ASPEK SYARIAH DALAM AUDIT LEMBAGA KEUANGAN ISLAM - Khairunisa, Fadia; Rahman, Taufik (Jurnal Akuntansi, Auditing dan Investasi, 2025)
ABSTRACT This research discusses sharia aspects in the audit of Islamic financial institutions by highlighting the importance of sharia audits as the main pillar that differentiates sharia financial institutions (LKS) from conventional financial institutions. The main problem raised was the low level of public trust in LKS' sharia compliance, which prompted the need for a sharia audit to ensure accountability and compliance with sharia principles. This research uses a literature study method by collecting data from various related literature. The research results show that sharia audits have a wider scope than conventional audits, covering financial, operational, social and environmental aspects, and emphasize the importance of the role of competent and independent sharia auditors. Sharia audits not only ensure that financial reports comply with sharia principles, but also assess an institution's ethical and social compliance. The conclusion of this research confirms that sharia audits are very important to maintain public trust, increase transparency, and ensure that LKS operations are in accordance with maqasid al-syariah, so that they can increase the reputation and competitiveness of sharia financial institutions in Indonesia. Key words: sharia audit, sharia financial institutions, sharia compliance, maqasid al-syariah, sharia auditor